“If it is too inconvenient I'm not going after it:” Convenience as a critical factor in information-seeking behaviors - Connaway, Lynn Sillipigni; Dickey, Timothy J.; Radford, Marie L. (Library & information science research, 2011)
In today's fast-paced world, anecdotal evidence suggests that information tends to inundate people, and users of information systems want to find information quickly and conveniently. Empirical evidence for convenience as a critical factor is explored in the data from two multi-year, user study projects funded by the Institute of Museum and Library Services. The theoretical framework for this understanding is founded in the concepts of bounded rationality and rational choice theory, with Savolainen's (2006) concept of time as a context in information seeking, as well as gratification theory, informing the emphasis on the seekers' time horizons. Convenience is a situational criterion in peoples' choices and actions during all stages of the information-seeking process. The concept of convenience can include their choice of an information source, their satisfaction with the source and its ease of use, and their time horizon in information seeking. The centrality of convenience is especially prevalent among the younger subjects (“millennials”) in both studies, but also holds across all demographic categories—age, gender, academic role, or user or non-user of virtual reference services. These two studies further indicate that convenience is a factor for making choices in a variety of situations, including both academic information seeking and everyday-life information seeking, although it plays different roles in different situations. ►User convenience is a major research finding, in all information-seeking situations. ►Users satisfice information needs, finding resources that are quick and good enough. ►Ease of direct access to information resources is very important. ►Time is an important situational factor, across demographic categories. ►Library systems should become more like the Web, and embedded in users' workflows.